From PKU Online Lessons for Dietetics Students to the PKU Sandwiches Album - Klaudia Konikowska; Renata Mozrzymas (MDPI AG, 2022)
The purpose of the manuscript is to present to academic teachers, doctors and nutritionists how practical online classes with dietetics students can be used to develop ready-made tools at work and for the education of phenylketonuria (PKU) patients and their caregivers/parents. During online classes in 2020, as part of the subject-diet therapy of metabolic blocks, 53 students prepared PKU sandwiches at home. Each PKU sandwich has a calculated nutritional value, and phenylalanine exchanger content, but does not include low-protein bread. The selection of a particular type of PKU bread depends solely on the PKU patient, hence it was deliberately not included in the calculations. The sandwiches, made by students and assessed by academic teachers, will be published with the following title "The PKU Sandwiches Album". The Album with more than 400 colorful pictures of PKU sandwiches, will be expected to inspire patients and help them add appeal to their diet, enriching it with new tastes, at the same time facilitating the memorizing process of ingredients, thanks to visualization and presented calculations, and motivating them to comply with strict dietary recommendation. The same nutritional calculations and ideas for sandwiches, with the use of different bread, e.g., gluten-free, may be useful in other diseases, such as celiac disease.